RELATIONSHIP BETWEEN PRINCIPALS LEADERSHIP PRACTICES, TEACHERS PROFESSIONAL COMMUNITIES & ORGANIZATIONAL COMMITMENT - Sharma, Sailesh (PEOPLE: International Journal of Social Sciences, 2019)
This study attempts to identify the relationship between perception of teachers on leadership practices of their principals, teacher’s professional communities and teachers’ organizational commitment in private secondary schools in National Capital Region in India. To identify the relationship between three variables, survey is conducted in thirty reputed private schools in National Capital Region of India. A survey instrument is developed using different theoretical perspectives from instructional leadership, transformational leadership combined as leadership for learning, teachers professional learning communities and organizational commitment in schools. This survey instrument is used as rating scale comprising different constructs of all the three variables. The instrument is subjected to pilot testing for reliability analysis and validity on a sample of at hundred teachers. The instrument is administered on 450 teachers from 30 selected schools and data obtained is subjected to analysis using SPSS. The findings reveal that teachers have perceived leadership for learning practices of their principals at moderate level. Teachers have also perceived their organizational commitment and teachers’ professional community at moderate level. It is also found that all of the three variables under study are moderately correlated with each other.